Penggunaan Dalil Hadis Mȃl Al-Mustafad Dan Qiyȃs Dalam Penetapan Ketentuan Hukum, Haul Dan Nisab Zakat Profesi - Y Yusefri (Institut Agama Islam Negeri (IAIN) Curup, 2017)
This article essentially conducts a critical study of the hadîth of mâl al-mustafâd which is used as the proposition of the law of obligatory zakat of profession, and the use of qiyâs as the proposition set the rules of haul, nisab and rate zakat profession. This study is interesting and important because there are differences in the opinions of ulama in solving some of these issues, which are assumed by their differences in the use of legal arguments (al-adillat al-syar'iyat), among them hadîth and qiyâs. The analysis of the hadith of mâl al-mustafâd uses the method of analysis of takhrîj al-hadîts. While the analysis on the use of qiyas uses the approach of ushûl al-fiqh method. The results of this study show that first, hadith on mâl al-mustafâd quality dha'îf (weak). However, since it has several channels of sanad transmistion, the quality rises to the hasan lighairihi, and therefore valid as the basis and legal evidence of zakat profession. Secondly, set the rule of haul, nisab, and rate zakat profession by using qiyâs to zakat gold, more precisely than qiyâs to zakat agriculture.